Universalisme Paulus Menurut Alain Badiou: Uraian dan Tantangan - Yasintus T. Runesi (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACT: When people believe that social particularities raise plurality of views in the contemporary society, Badiou introduces the idea of the universality of the singular subject with the aim of overcoming the so-called global village without solidarity. This article is a description of Badious thought, which is included in the line of thinkers which moves "small boat of thought" to the subject and the subjectivity of human. In the first section, I will outline Badious view about the problem of homogenization, followed by his view of Christianity as an event, which will lead us to his view on the universal singularity that is rooted in the proclamation of St. Paul. At the end, I will propose a critical note on his views in comparison with some philosophers who also spoke about St. Paul. This paper will be closed with a conclusion on the significance of Badious thought, in the context of contemporary society's pluralism, especially in Indonesia. KEYWORDS: Badiou, St. Paul, universality, singular subject, pluralism.